2020
DOI: 10.1051/0004-6361/202038437
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evolution during the formation of a protoplanetary disk

Abstract: Context. The chemical composition of protoplanetary disks is expected to impact the composition of the forming planets. Characterizing the diversity of chemical composition in disks and the physicochemical factors that lead to this diversity is consequently of high interest. Aims. The aim of this study is to investigate the chemical evolution from the prestellar phase to the formation of the disk, and to determine the impact that the chemical composition of the cold and dense core has on the final composition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 88 publications
(135 reference statements)
0
13
0
Order By: Relevance
“…See Table C1 for the references. Simulations have suggested that methanol mainly forms during the prestellar phase (Drozdovskaya et al 2015;Coutens et al 2020). If the fractional abundance of methanol is comparable among the hot corinos, one would also expect that the total number of gas-phase methanol is positively correlated with the bolometric luminosity based on the correlation between the extent of methanol and the bolometric luminosity.…”
Section: Luminosity and Warm Region In Hot Corinomentioning
confidence: 99%
“…See Table C1 for the references. Simulations have suggested that methanol mainly forms during the prestellar phase (Drozdovskaya et al 2015;Coutens et al 2020). If the fractional abundance of methanol is comparable among the hot corinos, one would also expect that the total number of gas-phase methanol is positively correlated with the bolometric luminosity based on the correlation between the extent of methanol and the bolometric luminosity.…”
Section: Luminosity and Warm Region In Hot Corinomentioning
confidence: 99%
“…This shift of the peak from the center can arise by considering highly asymmetric spiral arms, unlike those shown by our RHD model. For instance, recent non-ideal MHD simulations presented by Coutens et al (2020) showed a spiral arm pattern, produced by considering the collapse of a non-rotating 1 M core initialized with turbulence. Such an asymmetric structure, likely produced by the effect of the initial turbulent velocity field and magnetic field could explain the shift of the peak observed toward source B.…”
Section: The Origin Of the Observed Asymmetrymentioning
confidence: 99%
“…In many studies of chemical modeling in disks (e.g., Walsh et al 2015;Bosman et al 2018b), initial chemical abundances were assumed to be inherited from dark clouds, pre-stellar cores, and protostellar envelopes, and they are water-rich, on the basis of previous observations (e.g., Visser et al 2009Visser et al , 2011Boogert et al 2015). However, whether the disk chemical evolution is started from initial abundance conditions of the chemical reset (by e.g., irradiation, accretion shocks) or the inheritance from the dark clouds and protostellar envelopes is an important question (e.g., Yoneda et al 2016;Coutens et al 2020;Jørgensen et al 2020;van't Hoff et al 2020;Öberg & Bergin 2021). Eistrup et al (2016Eistrup et al ( , 2018 and Notsu et al (2020) discussed that the chemical abundances in Class II disks are strongly affected by ionisation rates in disks and the adopted initial molecular abundances (inheritance or reset).…”
Section: Chemical Evolution From Envelopes To Disksmentioning
confidence: 99%